How sport changed my life? Description of the perceived effects of the experiences of young Colombians throughout a sport for development and peace program - Gadais, Tegwen; Varela Pulido, Natalia; Soto, Victoria; Vinazco, Sandra; Garzon, Mauricio (Frontiers in Sports and Active Living, 2023)
Introduction This study contributes to the advancement of the field of Sport for Development and Peace (SDP) research in Latin America and the Caribbean (LAC). There are still few studies on SDP programs in this region and it is important to document and understand the impacts of these programs on participants. Methods The present study is the result of a collaborative research that aims to describe the experiences and perceptions of Colombian youth and program managers who participated in an SDP program that took them from a local community sports club to the Olympic Games. Seven semi-structured interviews were conducted with key actors (administrators, coaches, and athletes) who participated in a triple and transversal (local, district and national) Olympic walking training program. Results The results provided a better understanding of the program dynamics in the local, regional, and national level, as well as of the short- and long-term effects perceived by the actors of the process on their development, education, health, and career. Recommendations are made for SDP organizations in LAC. Discussion Future studies should continue to investigate the SDP initiative in LAC to understand how sport can help development and peace building in this region.